SEAweb: the small RNA Expression Atlas web application. Issue Volume 48:Issue D1(2020) (10th October 2019) - Rahman, Raza-Ur; Liebhoff, Anna-Maria; Bansal, Vikas; Fiosins, Maksims; Rajput, Ashish; Sattar, Abdul; Magruder, Daniel S; Madan, Sumit; Sun, Ting; Gautam, Abhivyakti; Heins, Sven; Liwinski, Timur; et al.
Abstract: We present the Small RNA Expression Atlas (SEAweb), a web application that allows for the interactive querying, visualization and analysis of known and novel small RNAs across 10 organisms. It contains sRNA and pathogen expression information for over 4200 published samples with standardized search terms and ontologies. In addition, SEAweb allows for the interactive visualization and re-analysis of 879 differential expression and 514 classification comparisons. SEAweb's user model enables sRNA researchers to compare and re-analyze user-specific and published datasets, highlighting common and distinct sRNA expression patterns. We provide evidence for SEAweb's fidelity by (i) generating a set of 591 tissue specific miRNAs across 29 tissues, (ii) finding known and novel bacterial and viral infections across diseases and (iii) determining a Parkinson's disease-specific blood biomarker signature using novel data. We believe that SEAweb's simple semantic search interface, the flexible interactive reports and the user model with rich analysis capabilities will enable researchers to better understand the potential function and diagnostic value of sRNAs or pathogens across tissues, diseases and organisms.